NLRP3 inflammasome in digestive diseases: From mechanism to therapy - Qiang, Rui; Li, Yanbo; Dai, Xincan; Lv, Wenliang (Frontiers in Immunology, 2022)
Digestive system diseases remain a formidable challenge to human health. NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome is the most characteristic multimeric protein complex and is involved in a wide range of digestive diseases as intracellular innate immune sensors. It has emerged as a research hotspot in recent years. In this context, we provide a comprehensive review of NLRP3 inflammasome priming and activation in the pathogenesis of digestive diseases, including clinical and preclinical studies. Moreover, the scientific evidence of small‐molecule chemical drugs, biologics, and phytochemicals, which acts on different steps of the NLRP3 inflammasome, is reviewed. Above all, deep interrogation of the NLRP3 inflammasome is a better insight of the pathomechanism of digestive diseases. We believe that the NLRP3 inflammasome will hold promise as a novel valuable target and research direction for treating digestive disorders.